Guardians of the game: UV-specific skin cancer prevention by coaches in outdoor sports - Leer, Sophie; Ehls, Clara; Schneider, Sven (Photodermatology, photoimmunology & photomedicine, 2025)
Background Due to the global rise in UV radiation, the prevalence of skin cancer is increasing significantly, with outdoor athletes being identified as a particularly vulnerable population group. Methods This nationwide, cross-sectional study was conducted among adult coaches from the 10 largest outdoor sports associations in Germany. Their applied prevention measures and the potential for further improvement in prevention were evaluated by guideline based scores (range [0-100]). Additionally, sport-, coach-, and club-specific variables were analysed and barriers that prevent comprehensive UV prevention were identified. Results The UV prevention practice of the 1200 participating coaches averaged 53.43 ± 16.37 [0.00-95.31], while the potential UV prevention options were assessed at a comparatively higher value of 58.82 ± 17.53 [0-100]. Notably, the proper use of sunscreen emerged as the most neglected preventive measure. Coaches identified the greatest potential for improvement in sunscreen renewal, water-resistant sun protection products and sunglasses. The study also revealed significant differences in UV protection practices between different sports, with soccer, tennis, and swimming exhibiting the most pronounced deficits. Factors such as coach qualification and experience, as well as club size and the size of training groups influenced the level of UV protection implemented. Many coaches cited various implementation obstacles such as fixed training times and resource constraints. Conclusion The study highlights specific areas for improvement in UV protection practices in outdoor sports, considering differences on sport, coach, and club levels. The significant number of active athletes in these sports underscores the public health importance of addressing UV protection in this field.